2009
DOI: 10.1007/s10562-008-9827-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on Methanethiol Synthesis from H2S-Rich Syngas Over K2MoO4 Catalyst Supported on Electrolessly Ni-Plated SiO2

Abstract: Small amount of Nickel deposited on SiO2 support by electroless plating was verified to have a significant promoting effect on the catalytic performance of the K2MoO4/SiO2 catalyst for methanethiol synthesis from H2S-rich synthesis gas. The addition of Nickel was found to be in favor of the suppression of the CO2 formation. The results of BET, TPR and Raman characterizations for the Ni-modified SiO2 and the catalyst K2MoO4/Ni-SiO2 showed that the surface properties of Ni-modified SiO2 were similar to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Promoted , and unpromoted MoS 2 are the active and stable catalysts for the WGS reaction in the presence of H 2 S. Moreover, K-MoS 2 has been utilized to synthesize CH 3 SH from CO + H 2 + H 2 S mixture and for the production of alcohols from syngas . CO is a vital platform chemical for the production of methanol or long-chain hydrocarbon via Fischer–Tropsch synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Promoted , and unpromoted MoS 2 are the active and stable catalysts for the WGS reaction in the presence of H 2 S. Moreover, K-MoS 2 has been utilized to synthesize CH 3 SH from CO + H 2 + H 2 S mixture and for the production of alcohols from syngas . CO is a vital platform chemical for the production of methanol or long-chain hydrocarbon via Fischer–Tropsch synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Baltrusaitis et al [26] proposed conversion of a CH 4 + H 2 S mixture into CH 3 SH and H 2 using light of a low wavelength (205 nm), potentially overcoming the large barrier for H 3 C H bond breaking via conical intersection related relaxation. Syngas in the presence of H 2 S has been converted to CH 3 SH [34][35][36], and the same has been achieved using CO + H 2 S mixtures [37,38]. Finally, Barrault et al [39] showed selective transformations of both CO and CO 2 in the presence of H 2 S and H 2 to CH 3 SH over K promoted WO 3 /Al 2 O 3 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, the reaction routes for the formation of methanethiol mainly include CH 3 OH-H 2 S reaction method [1][2][3][4], H 2 S-containing synthesis gas conversion method [5][6][7][8], CH 3 SCH 3 -H 2 S conversion method [9][10][11], and COS-H 2 S-H 2 conversion method [12,13] and so on.…”
Section: Introductionmentioning
confidence: 99%